2007
DOI: 10.1097/mbp.0b013e3280f813d0
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Omron M6 (HEM-7001-E) upper-arm blood pressure measuring device according to the International Protocol in adults and obese adults

Abstract: It was concluded that the Omron M6 device, which measures BP at the upper arm, was deemed to be in accordance with the International Protocol criteria and can be recommended for use by adults and obese adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 14 publications
1
29
1
2
Order By: Relevance
“…In spite of the systematic pattern in the Omron HEM-705 CP errors, the magnitude of the bias was small, less than 3 mmHg in almost all patient groups. Although other devices have shown an increment in the size of the bias in obese people for both systolic and diastolic blood pressure 10 , our results only support this increment for systolic blood pressure.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In spite of the systematic pattern in the Omron HEM-705 CP errors, the magnitude of the bias was small, less than 3 mmHg in almost all patient groups. Although other devices have shown an increment in the size of the bias in obese people for both systolic and diastolic blood pressure 10 , our results only support this increment for systolic blood pressure.…”
Section: Discussioncontrasting
confidence: 99%
“…Although statistically significant, these differences are very small and should have little impact in the clinical setting or in epidemiologic studies. Our results are consistent with those of some 10,11 , but not all studies on other Omron devices [12][13][14][15] . We also found that the Omron HEM-705 CP qualifies as a grade A device for measuring blood pressure, according to the BHS protocol criteria 1,2 .…”
Section: Discussionsupporting
confidence: 93%
“…11,12 Moreover, the M5 underwent validation procedures for elderly and for obese patients. 13,14 The R5 was validated by the Deutsche Hochdruckliga. 15 Its standard cuff size is applied to wrist circumferences from 13.5 to 19.5 cm.…”
Section: Oscillometric Blood Pressure Measurementsmentioning
confidence: 99%
“…Quando a medida da circunferência do braço foi igual ou superior a 33cm, o sujeito foi incluído no grupo dos obesos e a medida da circunferência do braço foi realizada no ponto médio do braço (ALTUNKAN et al, 2007).…”
Section: Antropometriaunclassified
“…Foi utilizada uma braçadeira suporte, fornecida pelo próprio fabricante do aparelho, para aqueles trabalhadores que apresentaram a medida de circunferência de braço acima de 22cm e um manguito pequeno, para aqueles trabalhadores que apresentaram a circunferência de braço com medidas entre 17 e 22cm (ALTUNKAN et al, 2007).…”
Section: And ' ' (unclassified